High performing Napier grass genotypes for improved biomass yield and nutritional quality - CGIAR Research Program on Livestock (2019)
High performing genotypes, under moderate and severe drought stress conditions, have been identified from harvests across two dry seasons, for broader testing across systems and acroecologies. The list of these top performing Napier grass genotypes is not yet in the public domain.